Operation sisterhood - Rhuday-Perkovich, Olugbemisola (Crown Books for Young Readers, 2022)
Eleven-year-old Bo is used to it being just her and her mom in their cozy New York apartment, but when her mom gets married, Bo must adjust to her new sisters and a music-minded blended family that is much larger, louder, and more complex than she ever imagined.